Transformasi Nilai-Nilai Kehidupan pada Relief Candi Mendut: Analisis Sastra, Historis, dan Kultural untuk Pembelajaran BIPA bagi Mahasiswa Thailand - Rakha Dandi Pratama; Azzahra Syaharani Widya Dharma Putri; Faizzah Nur Atikah; Fathiya Fairuz Aqilah; Kundharu Saddhono (Departement of Mathematics Education, 2025)
This study explores the life values depicted in the Jataka reliefs of Mendut Temple and their integration into BIPA (Indonesian for Foreign Speakers) learning for Thai students. By employing qualitative methods and descriptive analysis, the research examines the Jataka reliefs as a medium to convey moral lessons and cultural diplomacy. The focus is on understanding how these reliefs embody universal values such as compassion, honesty, and perseverance, and their potential as educational tools in cross-cultural learning. The findings indicate that Thai students not only gain linguistic competence but also develop a deeper appreciation for Indonesian culture, fostering a mutual understanding between the two nations. This study highlights the significance of integrating cultural elements into language education as a means of promoting diplomacy and strengthening international relations.